Filipino teachers' compartmentalization ability, emotional intelligence, and teaching performance / Marivel B. Go ... [et al.] - Go, Marivel B.; Golbin Jr., Rodolfo A.; Velos, Severina P.; Bate, Glynne P. (Universiti Teknologi MARA, 2020)
Teachers, as individuals outside the classroom, deal with their problems, yet are still expected to display desirable dispositions during students’ interaction. Thus, the strategy for regulating thoughts and emotions is vital for effective teaching. This study aims to measure the Filipino teachers' problem compartmentalization ability, their level of emotional intelligence, and teaching performance, mainly when they experienced personal issues. It also seeks to determine the relationship among variables. Validated researcher-made and adopted instruments were administered to 160 randomly selected elementary and secondary public school teachers from Cebu Province, Philippines, with a response rate of 87.5%. The tools were subjected to validity and reliability tests. The gathered data were analyzed with descriptive and inferential statistics using SPSS. Findings revealed that Filipino teachers have a high ability to compartmentalize their problems and a high level of perceiving, understanding, managing, and using their emotions. They also display positive disposition when they are in the classroom showing their good performance despite personal issues. Statistically, Filipino teachers' emotional intelligence and their problem compartmentalization ability were positively and significantly correlated to their teaching performance. Hence, these approaches may be included by the school leaders in teachers' training for the improvement of their well-being.